Dynamics of microflora number and biochemical activity in typical chernozem under pesticides complex application - Naidonova, O. E. (AgroChemistry and Soil Science, 2020)
In a stationary field experiment during the growing season 2019, the dynamics of microbiological and biochemical indicators’ parameters of typical heavy loamy chernozem in the plots treated with a complex of pesticides was studied in comparison with the control, untreated plots. The state of microbial communities in the soil under winter wheat with a single application, and under corn with single and double application of mixtures of several modern herbicides, fungicides and insecticides was assessed. The state of the microflora was monitored three times during the growing season according to the parameters of the number of microorganisms of various ecological-functional and taxonomic groups, the enzymatic activity of the soil, and integrated biological indices. At first, 1 and 4 days after the application of pesticides, the number of microorganisms and the activity of enzymes increased, but subsequently (after 3 weeks) the values of indicators decreased relatively untreated with pesticides soil. The number of microflora under wheat decreased by an average of 28 %, and under maize, which a week before the second sampling, they were treated with a mixture of pesticides for the second time – by 63 %. Five months after a single application of a complex of pesticides on winter wheat crops, the values of the number of microorganisms of certain groups in the soil were half, and some three times less than the corresponding values in the control variant. With an increase in the pesticide load (an increase in the frequency of treatments), the degree of inhibition of microflora increased. After two treatments of corn crops, the number of microflora and enzyme activity in the soil were significantly lower compared to the control, the degree of reduction was greater than with a single treatment of wheat. Over time, there was a gradual restoration of the biological properties of the soil, but even five months after two treatments of corn crops with pesticides, the number of microflora remained significantly lower than in the control. At the end of the growing season of both crops, the biological properties of typical chernozem did not reach the level of similar soil without the use of pesticides.